A Gas Chromatographic Method for the Determination of Bicarbonate and Dissolved Gases - Loughrin, John H.; Antle, Stacy W.; Polk, Jason (Frontiers in Environmental Science, 2017)
A gas chromatographic method for the rapid determination of aqueous carbon dioxide and its speciation into solvated carbon dioxide and bicarbonate is presented. One-half mL samples are injected through a rubber septum into 20-mL vials that are filled with 9.5 mL of 0.1 N HCl. A one mL portion of the headspace is withdrawn and injected onto a gas chromatograph equipped with a thermal conductivity detector. Using the dimensionless Henry's constant for carbon dioxide and an adaptation of the Henderson-Hasselbalch equation, carbon dioxide in the samples can be categorized among solvated, bicarbonate, and carbonate forms. Natural water samples as well as wastewater from a municipal sewage treatment plant and a swine rearing operation were analyzed by this method and the results compared favorably to those obtained by titration. Samples stored for up to 5 weeks showed no significant changes in carbon dioxide concentrations. In addition, using flame ionization and electron capture detectors, methane and nitrous oxide concentrations in the samples were also measured.